Strategies used by emergency care professionals to handle interpersonal difficulties with patients: a qualitative study. Issue 2 (8th February 2021) - Charrier, Philippe; Occelli, Pauline; Buchet-Poyau, Karine; Douplat, Marion; Delaroche-Gaudin, Marine; Fayard-Gonon, Florence; Jacquin, Laurent; Potinet, Véronique; Sigal, Alain; Tazarourte, Karim; Touzet, Sandrine
Abstract : Objectives: Identify the strategies implemented by emergency care professionals when facing tension and interpersonal violence from patients and their friends and family. Design: Descriptive qualitative study based on 38 semidirective interviews. Participants: Doctors, nurses, nursing assistants and administrative staff. Setting: Four emergency departments (EDs) from three French university hospitals. Results: According to the medical professionals interviewed, the difficulties that they encounter with patients or their accompanying family members can be explained by a lack of understanding of the functioning of EDs, by a general increase in individualistic behaviours leading to a lack of civility or by deviant behaviours (related to toxic substance abuse or mental illness). While managing deviant behaviours may sometimes require a collective intervention, ED staff also implement what are essentially individual communication strategies (with the use of rational explanation, seduction and empathy), confrontation or flight to deal with interpersonal difficulties. Conclusions: Strategies used by staff members tend to be individualised for the most part, and some, such as confrontational or escape strategies, may not be adapted to all situations. In the face of difficulties between staff and patients, mediators, specialised in resolving conflict, could entrust some cases to professionals. Trial registration number: ClinicalTrials.gov Registry (NCT03139110 ).